2018
DOI: 10.1111/coa.13231
|View full text |Cite
|
Sign up to set email alerts
|

Snoring sound energy as a potential biomarker for disease severity and surgical response in childhood obstructive sleep apnoea: A pilot study

Abstract: Objective To investigate the relationship between baseline snoring sound energy (SSE) and disease severity, changes in SSE after adenotonsillectomy, and the predictors of surgical success in children with obstructive sleep apnoea (OSA). Design Prospective cohort study. Setting Tertiary referral medical centre. Participants Thirty‐two children with OSA whose apnoea‐hypopnoea index ≥5 or apnoea‐hypopnoea index ≥1.5 with OSA comorbidities were recruited. Patients with complicated OSA were excluded. All participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 25 publications
(53 reference statements)
0
23
0
Order By: Relevance
“…The best predictive models included age < 7.0 years, BMI z-score < 1.44, GM-CSF < 0.2 pg/mL, MCP-1 < 51.2 pg/mL, and RANTES > 15,435.5 pg/mL. Previous studies have reported that age [16,56], BMI z-score [16,56], and AHI [16,28,56,57] are predictors of post-AT AHI, in addition to asthma [16], OSA-18 [28], and snoring sound energy [28]. However, GM-CSF, MCP-1, and RANTES as a surgical outcome predictor have never been reported.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The best predictive models included age < 7.0 years, BMI z-score < 1.44, GM-CSF < 0.2 pg/mL, MCP-1 < 51.2 pg/mL, and RANTES > 15,435.5 pg/mL. Previous studies have reported that age [16,56], BMI z-score [16,56], and AHI [16,28,56,57] are predictors of post-AT AHI, in addition to asthma [16], OSA-18 [28], and snoring sound energy [28]. However, GM-CSF, MCP-1, and RANTES as a surgical outcome predictor have never been reported.…”
Section: Discussionmentioning
confidence: 93%
“…Paired Student's t-tests were used to compare changes in the variables 3 months postoperatively. Variables with a p-value < 0.05 in the Student's t and ANOVA tests were further dichotomized according to the optimal cut-off value using receiver operating characteristic curves [28]. The dichotomized variables were then assessed using multivariate logistic regression models.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to detect the severity of OSA with snoring sound analysis and used the MFCC, FF, and VI. Although the MFCC and FF were also used in past studies, they were not adequate for determining the severity of OSA [3,5,21]. U. R. Abeyratne et al used some of these features to investigate snore sounds for OSA/non-OSA classifications [22].…”
Section: Discussionmentioning
confidence: 99%
“…These complicated devices impose stress on not only patients but also clinical staff because they need to spend a long time connecting the patient to the equipment. For these reasons, although there are many patients with potential sleep apnoea, treatments for patients with potential sleep apnoea have not progressed [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation